Primary Extranodal Lymphoma – A Three Year Study in a Tertiary Care Centre - Bezbaruah, Rukmini; Choudhury, Arpan (Asian Pacific Journal of Cancer Care, 2025)
Introduction: Primary extranodal lymphoma ( pENL ) is a group of lymphomas arising from tissues other than lymph nodes. Although the incidence of extranodal non Hodgkin lymphoma (ENL) is increasing worldwide, data is minimal. Aims and objectives: To study the prevalence, anatomical distribution, clinical factors, and histological subtypes of extranodal lymphoma. Materials and methods: This was a retrospective observational study conducted in the Department of Oncopathology in a regional cancer centre where we retrieved 103 cases of primary extranodal lymphoma ( pENL ) out of 380 cases of lymphoma from the institute’s data registry that were diagnosed over a period of three years from January 2017 to December 2019. Result: There were 103 patients with primary extranodal lymphoma out of 380 patients with lymphoma, including 68 males and 35 females (M: F = 1.9:1), and the peak incidence occurred during the 4th to 5th decades of life. The age range was 4-80 years, and the mean age was 45.9 years. The median age was 50 years ± 19.2 years. The commonest site was the gastrointestinal tract (GIT) (31.8%), followed by the breast (15.5%). B-cell lymphoma was more common than T-cell lymphoma. The most frequent histopathological types of B-cell lymphoma were diffuse large B-cell lymphoma (DLBCL) (47%), Burkitt lymphoma (BL) (13%) and marginal zone lymphoma (MZL), (6%). Most of the patients in the pENL group were diagnosed to have Stage I/II lymphoma whereas Stage III/IV was more common in patients with nodal NHL. Most of the patients were treated with chemotherapy following the diagnosis. The most common chemotherapy used was cyclophosphamide, doxorubicin, vincristine, and prednisolone regimen, and rituximab was a part of chemotherapy. Conclusion: Primary extranodal lymphomas constitute a diverse group of haematolymphoid malignancies. The diagnosis is a frequent challenge for pathologists, due to their morphological, characteristics and varied clinical presentations. Immunohistochemistry plays a major role in the diagnosis of primary extranodal lymphoma. Compared to the published series, no difference was noted regarding sex predilection or morphology. However, as this was mostly an epidemiological and morphological study, data about the detailed therapeutic outcomes are lacking.